ANALISIS KESULITAN SISWA SMA DALAM MENJAWAB SOAL MATEMATIKA PEMINATAN - Hadi Harianto; Ainul Yakin (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2022)
The purpose in the research to describe the troublewhich class student experienced by XI SMAN 1 Woha Bima in resolving the mathematical supplylimit material in particular.This type of research is a description qualitative study, the research inapril month SMAN 1 Woha Bima. Subjek in the research is class student XI SMAN 1 Woha Bima which is comprised of 19 students. The instrument used in the research is tets using a 5 number essay for knowing the layout trouble student and interview for know what cause trouble student. Based on data analysis and discussion it can be conclusion that (1) the study trouble in tets number 1a the presentation is as much (28,57%) based on interview that mots students had trouble with the concept of a mathematical operation wich would have to finish first (2) the study trouble in tets number 1a the presentation is as much (7,14%) based on interview that student trouble in number 1b because trouble in deciphering the number of degrees in algebra, (3) the study trouble in tets number 1a the presentation is as much (14,28%) from a student’s analysis of answers that the student’s trouble in answering the number 1c is consistent with the trouble experienced in number 1b, (4) the study trouble in tets number 1a the presentation is as much (50%) from a students analysis of answer that the student’s and interview the feeling student’s trouble in algebra forms, (5) ) the study trouble in tets number 1a the presentation is as much (7,14) from a student’s analysis and interview trouble that what student experienced was two in describing the shape of algebra and the trouble in changing roots.